Perbandingan Aktivitas Antioksidan Senyawa Flavonoid dari Ekstrak Daun Kelor (Moringa Oleifera L.) Menggunakan Metode Spektrofotometri Uv-Vis - Puteri Rahma Maharani; Izmi Haura Syahida; Munir Alinu Mulki (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The bioactive compounds found in moringa leaves (Moringa oleifera L.) can function as natural antioxidants to protect cells from damaging free radicals. The purpose of this study is to ascertain the antioxidant activity of moringa leaves according to the type of solvent, analyze the relationship between antioxidant capacity and concentration of active compounds, and determine the best solvent. Extraction was carried out using ethanol, methanol, and aquades solvents, followed by testing antioxidant activity using UV-Vis spectrophotometry method on DPPH radicals. The content of phenols, flavonoids, and tannins in the extract was measured to understand their contribution to antioxidant activity Based on the results of the study, the extract containing ethanol solvent showed the most powerful antioxidant activity, with an IC50 value of 103.98 ppm. In conclusion, the type of solvent has a significant effect on the antioxidant activity of moringa leaves, with ethanol solvents being the most effective option. This research strengthens the potential of moringa leaves as a natural source of antioxidants that can be utilized for applications in the pharmaceutical and health fields, although further research is needed to optimize extraction techniques and the development of moringa oleifera leaf-based product